Molecular Engineering of Polymyxin B for Imaging and Treatment of Bacterial Infections - Wu, Minghao; He, Shipeng; Tang, Hua; Hu, Honggang; Shi, Yejiao (Frontiers in Chemistry, 2022)
The emergence of multi-drug resistant bacteria and the lack of novel antibiotics to combat them have led to the revival of polymyxin B, a previously abandoned antibiotics due to its potential nephrotoxicity and neurotoxicity. To facilitate its widely clinical applications, increasing effort has been devoted to molecularly engineer polymyxin B for the targeted imaging and effective treatment of bacterial infections. Herein, the molecular engineering strategies will be summarized in this mini review, with selected recent advances for illustration. Perspective of the challenges and trends in this exciting and eagerly anticipated research area will also be provided in the end. We hope this mini review will inspire researchers from diverse fields to bring forward the next wave of exploiting molecular engineering approaches to propel the “old” polymyxin B to “new” clinical significance in combating bacterial infections.